Reinforcing Collaboration and Harmonization to Unlock the Potentials of Advanced Therapy Medical Products: Future Efforts Are Awaited From Manufacturers and Decision-Makers - Tingting Qiu; Shuyao Liang; Yitong Wang; Claude Dussart; Borislav Borissov; Mondher Toumi (Frontiers Media S.A., 2021)
Some advanced therapy medicinal products (ATMPs) hold great promises for life-threatening diseases with high unmet needs. However, ATMPs are also associated with significant challenges in market access, which necessitates the joint efforts between all relevant stakeholders to navigate. In this review, we will elaborate on the importance of collaborations and harmonization across different stakeholders, to expedite the market access of promising ATMPs. Manufacturers of ATMPs should proactively establish collaborations with other stakeholders throughout the whole lifecycle of ATMPs, from early research to post-market activities. This covered engagements with (1) external developers (i.e., not-for-profit organizations and commercial players) to obtain complementary knowledge, technology, or infrastructures, (2) patient groups and healthcare providers to highlight their roles as active contributors, and (3) decision-makers, such as regulators, health technology assessment (HTA) agencies, and payers, to communicate the uncertainties in evidence package, where parallel consultation will be a powerful strategy. Harmonization between decision-makers is desired at (1) regulatory level, in terms of strengthening the international standardization of regulatory framework to minimize discrepancies in evidence requirements for market authorization, and (2) HTA level, in terms of enhancing alignments between regional and national HTA agencies to narrow inequity in patient access, and cross-border HTA cooperation to improve the quality and efficiency of HTA process. In conclusion, manufacturers and decision-makers shared the common goals to safeguard timely patient access to ATMPs. Collaboration and harmonization will be increasingly leveraged to enable the value delivery of ATMPs to all stakeholders.